Dominican Republic : Staff Report for the 2009 Article IV Consultation and Request for a Stand-By Arrangement; Supplement to the Staff Report and Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
This 2009 Article IV Consultation highlights that the Dominican Republic's economy has been adversely affected by the global crisis. Output has been below potential as real GDP growth is decelerating rapidly from more than 5 percent in 2008 to an estimated 0.5 percent to 1.5 percent in 2009. Monetary authorities have responded to the crisis in a timely manner. The authorities' program aims to limit the effects of the global slowdown on the economy while establishing the conditions for robust and sustainable growth.